Need for follow up in coeliac disease. Issue 3 (March 1994) - Bardella, M T; Molteni, N; Prampolini, L; Giunta, A M; Baldassarri, A R; Morganti, D; Bianchi, P A
Abstract : The use of follow up studies was evaluated in 128 patients with coeliac disease during their first visit to a department for adults. The original diagnosis had been made in childhood in all patients. Fifty eight (45%) of the subjects were following a gluten free diet, 23 (18%) were following a gluten free diet but with occasional gluten consumption, and 47 (37%) had adopted an unrestricted, gluten containing diet for a mean of 11.2 years. There was no correlation in individual subjects between the presence of symptoms, biochemical and immunological abnormalities, severity of histological findings, and the amount of dietary gluten, despite the greater frequency of symptoms in the group following an unrestricted diet than in the other two groups. Short stature and epilepsy with cerebral calcifications only occurred in patients following an unrestricted diet. As only diagnosis based on two or three biopsy samples and regular follow up correlated positively with dietary compliance, it is suggested that a histologically confirmed diagnosis of coeliac disease and regular lifelong follow up are essential in the management of these patients.